Citoyenneté féminine sous la Seconde République : entre le réformisme social et la démocratisation - Ana Aguado (Cahiers de Civilisation Espagnole Contemporaine)
The Spanish Second Republic brought modernising changes but also continuities in gender relations, as well as legal reforms and cultural resistances. This process of democratisation -with its contradictions and its limits- was possible in a new political and legislative context. In addition to the achievement of women's suffrage, the republican government adopted, between May 1931 and the summer of 1933, seventeen legal texts related to equality between men and women and women’s civil and political rights, along with their inclusion into public life. All these rights, as well as the right to vote, were included in the Constitution of 1931. The new republican regime therefore created the necessary conditions -although still insufficient- for women to redefine egalitarian concepts found in certain political cultures, such as republicanism or socialism, with a gender approach. It was this redefinition that initiated a process of construction of new gender identities.